The enhancing effects of Biobran/MGN-3, an arabinoxylan rice bran, on healthy old adults' health-related quality of life: a randomized, double-blind, placebo-controlled clinical trial. - Elsaid, A. F.; Fahmi, R. M.; Shaheen, M.; Ghoneum, M. (Quality of Life Research, 2020)
Purpose: The world's older population is growing rapidly and the need to find measures to combat age-associated decline of physical, mental, and cognitive functions and improve their health-related quality of life (HRQOL) is escalating. Biobran/MGN-3, an arabinoxylan rice bran, has been previously reported to improve the quality of life in cancer patients. The objective of the current study was to examine the effect of a low dose of Biobran/MGN-3 supplementation on the HRQOL in a healthy older adult population.Methods: Sixty apparently healthy subjects, 40 males and 20 females, over 56 years old were recruited and blindly randomized into two group receiving either placebo or Biobran/MGN-3 (250 mg/day for 3 months). Participants did not take any vitamins or medications during the study and their health was closely monitored. HRQOL was assessed at the initiation and termination of the study using the previously validated Arabic version of SF-12v2 questionnaire.Results: For all measured HRQOL domains, there was no statistically significant difference in baseline scores between the two groups. Compared to baseline values and placebo-treated subjects, Biobran/MGN-3 supplementation significantly enhanced the levels of physical and mental component summary scores as well as role-physical, bodily pain, vitality, and social functioning subdomain scores.Conclusion: These results show that Biobran/MGN-3 is a promising psychoneuroimmune modulatory agent that could improve the HRQOL in healthy old adults.